Utilização de lama vermelha para oxidação eletrolítica assistida por plasma de liga de alumínio - Sottovia, Livia [UNESP] (2015)
Red mud is an alkaline residue of Bayer process, discarded by industry, which can contaminate groundwater and surface water, beyond the risk of containment burst. It contains Al, Ca, Si, Fe and Ti oxides and for its characteristics has been studied in different areas. Recently, some studies have reported its use as a metal couting. Plasma Electrolytic Oxidation (PEO) is an emerging tecnique highly employed in industry for external ans internal recovery, once this technique allows the recovery of any geometry and being no environmental harmful. Thus, for its characteristics, red mud was studied as 5052 aluminum alloy coating through the plasma electrolytic deposition technique, to protect against wear, and also to add value to this residue. The design of experiments followed the factorial 2, where the following parameters were varied: frequency (200 and 300 Hz), deposition time (10 and 20 minutes) and concentration of the electrolyte solution, composed of red mud (1 and 5 g/L). The voltage voltage was kept constant at 600 V for all depositions, the duty cycle was 60% for all depositions as well. Red mud was analyzed by Scanning Electron Microscopy and Spectroscopy Energy Dispersive (SEM/EDS), X-Ray Diffraction (XRD) and Infrared Spectroscopy (FTIR). This coating were analyzed by SEM/EDS, XRD, FTIR, roughness, wettability, surface energy, eddy current and wear testing with pin-on-disk. Red mud consists of C, O, Na, Al, Si, Ca, Ti, Fe, S and P, in rutile, hematite, magnetite, goethite, gibbsite, quartz, silicon oxide, alumina, kaolinite, sodalite and calcite phases. The coatings are composed of O, Mg, Na, Al, Si, Ca, Ti, Fe, S and P. The phases of metallic aluminum, allumina, iron, titanium, spinel and iron titanium were identified. Although, in two series, alpha alumina may have occurred. The FTIR analysis showed presence of Al-O, Si-O, Si-Al-O, O-H and Fe-O bondings. The coatings increased the roughness of the substrate, ranging from 0.33...